Correlation between Milk Chocolate Consumption Habit and Chronotype with Gingivitis in Children with Mixed Tooth Period - Fahmi, Muhammad Izzul Widad; Cilmiaty, Risya; Nurwati, Ida (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Children in the mixed dentition period are prone to oral health problems. This can be caused by the frequent consumption of milk chocolate and the child's chronotype being the night type. This study aims to determine the relationship between milk chocolate consumption habits and chronotype with gingivitis in children with mixed dentition. The study used a survey method with a cross-sectional approach. The population of this study were Madrasah Ibtidaiyah (MI) students in the Situbondo district aged 6-12 years with 100 students from 9 MI subjects. Determination of schools using multistage random sampling and selecting subjects using proportional random sampling. The questionnaires used were the Children Chronotype and Semi-Quantitative Food Frequency Questionnaire. Gingival index examination is performed by a dentist. Data analysis used the Pearson statistical test at a significant level a= 0.05. The results showed that 49% of children had a moderate gingival index and 5.8% had a severe gingival index. As many as 23% of children often consume milk chocolate and 13% of children are included in the evening chronotype category. Statistical test results showed a positive correlation between milk chocolate consumption habits and gingivitis (p-value 0.021) and a positive relationship between chronotype and gingivitis (p-value 0.015). In conclusion, there is a correlation between milk chocolate consumption habits and gingivitis and there is a relationship between chronotype and gingivitis in mixed dentition children. Abstrak: Anak yang memasuki periode gigi bercampur rentan mengalami masalah kesehatan rongga mulut. Hal ini dapat disebabkan karena seringnya konsumsi cokelat susu dan beralihnya kronotipe anak menjadi tipe malam. Penelitian ini bertujuan untuk mengetahui keterkaitan antara kebiasaan konsumsi cokelat susu dan kronotipe dengan gingivitis pada anak periode gigi bercampur. Penelitian menggunakan metode survei dengan pendekatan cross sectional. Populasi penelitian ini adalah siswa Madrasah Ibtidaiyah (MI) di kabupaten Situbondo yang berusia 6-12 tahun dengan subjek sebanyak 100 siswa dari 9 MI. Penentuan sekolah menggunakan multistage random sampling dan pemilihan subjek menggunakan proportional random sampling. Kuesioner yang digunakan adalah Children Chronotype Questionare dan Semi Quantitative Food Frequency Questionare. Pemeriksaan indeks gingiva dilakukan oleh dokter gigi. Analisis data menggunakan uji statistik Pearson pada taraf signifikan a= 0,05. Hasil penelitian menunjukan bahwa 49% anak memiliki indeks gingiva sedang dan 5,8% parah. Sebanyak 23% anak sering mengkonsumsi cokelat susu dan sebanyak 13% anak termasuk kategori kronotipe malam. Hasil uji statistik menunjukkan bahwa ada korelasi positif antara kebiasaan konsumsi cokelat susu dengan gingivitis (p-value 0,021) dan ada hubungan positif kronotipe dengan gingivitis (p-value 0,015). Kesimpulannya terdapat korelasi antara kebiasaan konsumsi cokelat susu dengan gingivitis dan ada hubungan antara kronotipe dengan gingivitis pada anak periode gigi bercampur.